Propostas de implementações de aspectos metodológicos na utilização do 18F-FDG na tomografia por emissão de pósitron - Cássio Miri Oliveira (2013)
This work covered three objectives: to evaluate and implement methods for in vivo internal occupational monitoring of individuals involved during the 18F-FDG process production; to suggest a national Diagnostic Reference Level (DRL) for 18F-FDGPET oncologic procedures; and to obtain the Recovery Coefficients (RCs) factors used to correct the radiopharmaceutical uptake in region of interest for a better quantification and evaluation of images. The methodology of internal monitoring was implemented in the radiopharmaceuticals production centers of Nuclear Technology Development Center (CDTN) in Belo Horizonte MG and the Nuclear Science Regional Center, North-East (CRCN-NE) in Recife PE. The results demonstrated that the developed methodology was efficient to evaluate 18F-FDG incorporations in both centers; additionally, the methodology showed that there was possibility of 18F incorporation in the form of 18F-FDG during non-routine actions performed in the radiopharmaceutical production process. DRLs were suggested based on a questionnaire that was used for the survey of 18F-FDG administered activity in 72 Brazilian clinics currently licensed by the National Nuclear Energy Commission (CNEN). The results reported by 41 (57%) of the 18F-FDG-PET clinics showed variations up to 100% in the administered activities among clinics for the same procedure. The calculated DRL from the third quartile was 5.54 MBq/kg or 387.7 MBq (for a 70 kg standard patient). For image analysis, two phantoms were used for obtaining the RCs, the NEMA/IEC Body Phantom, which has spherical capture areas and the modified Jaszczak, which has cylindrical capitation capture areas. Both phantoms were tested for different lesion:BG activity ratios, in the amount of 4:1 and 10:1; for different acquisition time. RCs obtained according to NEMA and IEC standards were applied to the SUVmax and SUVmed semiquantification tools. Values of SUVmed corrected by RCs presented satisfactory results with the smallest differences (1.1 a 6.7%) in relation to the SUVreference values for both phantoms; even for different adopted acquisition time and different capture area geometries (spherical and cylindrical). However, it did not occur with corrected SUVmax values. This work contributed to a better knowledge of the 18FFDG- PET technique pointing mishaps and possible methodologies to repair them with the primary intention to cooperate for the radiological safety of occupational exposed individuals and patients health.